Factors associated with incomplete surgical margins in basal cell carcinoma of the head and neck - Girardi,Fábio Muradás (2021)
Abstract Introduction: Cutaneous basal cell carcinoma recurrence is associated with inadequate surgical margins. The frequency of and the factors associated with compromised or inadequate surgical margins in head and neck basal cell carcinoma varies. Objective: The purpose of this study was to evaluate the clinical and pathological factors associated with inadequate surgical margins in head and neck basal cell carcinoma. Methods: We developed a cross-sectional study comprising all patients who had undergone resection of head and neck basal cell carcinoma from January 2017 to December 2019. Data on age, sex, head and neck topography, histopathological findings, and staging were retrieved and compared. Each tumor was considered an individual case. Compromised and close margins were termed ‘‘inadequate’’ or ‘‘incomplete’’. Variables that were significantly associated with the presence of incomplete margins were further assessed by logistic regression. Results: In total, 605 tumors from 389 patients were included. Overall, sixteen cases (2.6%) were classified as compromised, 52 (8.5%) as close, and 537 (88.7%) as free margins. Presence of scleroderma (p = 0.005), higher Clark level (p < 0.001), aggressive variants (p < 0.001), invasion beyond the adipose tissue (p < 0.001), higher T stage (p < 0.001), perineural invasion (p = 0.002), primary site (p = 0.04), multifocality (p = 0.01), and tumor diameter (p = 0.02) showed association with inadequate margins. After Logist regression, multifocality, Clark level and depth of invasion were found to be independent risk factors for inadequate margins. Conclusion: Gross clinical examination may be sufficient for determining low prevalence of inadequate surgical margins when treating head and neck basal cell carcinoma in highly experienced oncologic centers. Multifocality, Clark level and depth of invasion were found to be independent risk factors for incomplete margins.